AQP4 autoantibodies in patients with idiopathic normal pressure hydrocephalus - Gastaldi, Matteo; Jarius, Sven (Journal of neuroimmunology, 2020)
Idiopathic normal pressure hydrocephalus (iNPH) is a common neurological disorder with unknown etiology. A selective depletion of aquaporin 4 (AQP4) has been shown in iNPH patients. We collected serum and cerebrospinal fluid (CSF) from 43 iNPH patients and 35 with other neurodegenerative conditions, and serum from 43 healthy subjects. All samples were tested for AQP4-IgG/IgA/IgM antibodies using a live cell-based assay. No patients or controls had serum/CSF AQP4-IgG/IgA. One/43 iNPH patient and 0/43 controls tested positive for serum AQP4-IgM. The AQP4-IgM-positive iNPH patient had no clinico-radiological distinctive features. AQP4 antibodies are unlikely to play a role in iNPH pathogenesis.
Gesehen am 04.01.2021